SOCIAL REGULATION OF THE A11 DOPAMINERGIC NUCLEUS IN ZEBRAFISH (Danio rerio) - Heagy, Faith K (East Carolina University, 2023)
Aggression is a universal behavioral feature that is present in majority of social animals. In nature, aggression facilities the formation and stabilization of social relationships and allow animals to divide resources according to rank. In zebrafish, aggressive interactions lead to stable dominance formation that consist of dominants and subordinates. Although social-status-dependent differences in behavior must arise due to neural plasticity, mechanisms of how neural circuits are reconfigured to cope with aggression and social stress are poorly described. Here, I describe how the hypothalamic dopaminergic A11 nucleus, is morphologically influenced by social status in male zebrafish. The A11 integrates and relays sensory social information to spinal motor circuits to modulate behavior; thus, the A11 is potentially prone to socially induced plasticity. I hypothesized that morphological plasticity of the A11 is differentially regulated in animals of different social ranks. I tested my hypothesis by combining non-invasive behavioral observations and histological approaches. Specifically, I used Tg(dat:eGFP) zebrafish, that specifically express eGFP in the dopaminergic system to investigate how dyadic agonistic interactions affect the A11 morphology and axosomatic network connectivity, then correlated morphological plasticity with changes in motor activity. I show that A11 cell number and synaptic connectivity are socially regulated. The number of A11 neurons increases in socially dominant animals as social relationships mature, while synaptic connectivity is increased in subordinates. Secondly, I show that these morphological differences are reversable as social environment evolves and correlate with adaptations in motor activity. Results from this project improve our understanding of how social dominance induces morphological plasticity of social decision-making networks and their influence on behavior.
Keywords: Hypothalamus; Social Regulation; Motor behaviors; Zebra danio--Behavior; Aggressive behavior in animals; Social hierarchy in animals; Dopamine--Receptors